Lazarillos bekendelse - Madsen, Peter (K&K - Kultur og Klasse, 2007)
Lazarillo’s Confession In Friedrich Schlegel’s ‘Letter on the Novel’ Fielding is opposed to Sterne, i.e. vulgar realism as opposed to spiritual form and inward imagination. The short anonymous novel about Lazarillo is here taken as an early specimen of novelistic realism and thus as part of the origin of the trend in the history of the genre, which is the object of Schlegel’s elitist scorn. At the background of depictions of contemporary poverty, Lazarillo de Tormes is read along the line of Humanist Christianity, represented by Vives. Various implicit references to the Bible are highlighted. At the level of form the autobiographical first-person narrative is seen in the light of confession and juridical testimony in a period strongly marked by the Inquisition.